Dizziness and syncope in young people: keep yourmind open! Case report of the challenging differentiation between arrhythmogenic right ventricular cardiomyopathy/dysplasia (ARVC/D) and catecholaminergic polymorphic ventricular tachycardia (CPVT) - Comelli, Ivan; Gonzi, Gianluca; Mossini, Gianluigi; Lippi, Giuseppe; Meschi, Tiziana; Borghi, Loris; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2014)
A paradigmatic case of aborted sudden cardiac death (SCD) in a young man is discussed, mirroring the challenge of diagnosing the various conditions potentially underlying this dramatic condition. Based on the clinical characteristics of our case, presenting some overlapping clinical features common to both the diseases, the discussion will be focused on Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) and Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia (ARVC/D). Epidemiological, genetic, diagnostic and therapeutic aspect will be discussed.